Pendampingan Penyusunan Program Pelatihan Digitalisasi Sekolah Berbasis Profil Kompetensi dan Analisis Kebutuhan - Suryo Prabowo; Mukti Amini; Nia Jusniani; Susy Puspitasari; Siti Muyaroah; Tepati Hak Kewajiban (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
School digitalization programs often encounter implementation challenges due to the absence of an accurate competency map of educators, resulting in capacity-building initiatives that are frequently misaligned with actual needs. This community service project aimed to assist school management in developing a draft of an adaptive technology training program based on empirical data. The program was implemented using a mixed diagnostic approach that combined the administration of an online digital readiness questionnaire with field validation through face-to-face focus group discussions. The activity involved all teaching staff of the partner school, consisting of twelve classroom teachers and one principal as active participants. The quantitative mapping results and qualitative confirmation revealed that, although teachers demonstrated a high level of ownership of personal digital devices, they faced significant challenges related to limited hardware storage capacity and difficulties in tracking revisions of administrative documents managed manually. Based on these identified issues, the project successfully formulated an official blueprint document for a school digitalization training program, which was jointly approved by the school management for future implementation. The primary benefits for the partner institution included the availability of a measurable staff capacity-development roadmap and increased collective awareness among teachers regarding the importance of transitioning toward cloud-based management systems. This community service initiative concludes that actively involving school stakeholders in diagnosing their internal needs can produce digitalization program designs that are more targeted, accurate, and widely accepted. The findings highlight the importance of data-driven planning as a foundation for sustainable school digital transformation.